The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/en13092211
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Study of Thermal Processes in Red Clays Exposed to High Temperatures

Abstract: Fired bricks represent one of the most popular building materials, of which production is still growing. Since the functional properties of bricks have reached their physical limits, the current development aims at an optimization of production procedures as it goes along with heavy environmental loads. This paper is focused on tailoring the firing procedure to optimize the energy demands. Dealing with five different clays, their heat storage properties are determined using inverse analysis of calorimetric dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The waste ceramic powder, generated in brick plant in Libochovice, Czech Republic, was used as precursor for alkaline activation. Its chemical composition (examined by XRF spectroscopy) is interesting, when compared by "common" red-clay ceramics, by relatively high content of CaO (table 1), what is due to the composition of the loess in Libochovice [12,13]. The phase composition of the precursor (table 2) represents a typical red-clay ceramicsit contains quartz and number of silicate minerals.…”
Section: Methodsmentioning
confidence: 99%
“…The waste ceramic powder, generated in brick plant in Libochovice, Czech Republic, was used as precursor for alkaline activation. Its chemical composition (examined by XRF spectroscopy) is interesting, when compared by "common" red-clay ceramics, by relatively high content of CaO (table 1), what is due to the composition of the loess in Libochovice [12,13]. The phase composition of the precursor (table 2) represents a typical red-clay ceramicsit contains quartz and number of silicate minerals.…”
Section: Methodsmentioning
confidence: 99%
“…The drying and firing processes of ceramic products are characterized by high energy consumption [14][15][16]. Silva et al [5] reported that the energy cost during the drying and firing stages has a considerable influence on the price of the final product, representing about 30% of the total average cost of production.…”
Section: Introductionmentioning
confidence: 99%
“…In the consulted literature, no studies were found that evaluated the drying process of ceramic materials at low temperatures (less than 50 • C). In addition, such works are limited to simpler geometries, such as hollow bricks and ceramic blocks [1,3,5,7,8,13,16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It was also noticed that the only operational parameter evaluated in the drying process of ceramic materials reported in the literature is the temperature of the drying air; parameters not being evaluated, for example, were cases involving the same temperature and different values for relative humidity and/or velocity, including dimensions variations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation